19.5k views
4 votes
6(r-4)-5(r-1)=2(r+6) r=?

User DjKianoosh
by
4.6k points

2 Answers

2 votes

Answer:

r = -31

Explanation:

The picture is how I solved it.

6(r-4)-5(r-1)=2(r+6) r=?-example-1
User Raupach
by
5.4k points
1 vote

Answer: r=-31

Explanation:

To find r, we want to use algebraic properties to isolate r.

6(r-4)-5(r-1)=2(r+6) [distribute]

6r-24-5r+5=2r+12 [combine like terms]

r-19=2r+12 [subtract both sides by 2r]

-r-19=12 [add both sides by 19]

-r=31 [divide both sides by -1]

r=-31

Now, we know that r=-31.

User Gabra
by
4.6k points